Vaccine-containing blister-free bait for oral immunization of carnivorous animals against rabies - D. V. Buchukuri; N. A. Kovalev; Y. V. Lamaka; D. S. Barysavets; S. V. Velikiy; D. O. Shpilevskiy; Д. В. Бучукури; Н. А. Ковалев; Ю. В. Ломако; Д. С. Борисовец; С. В. Великий; Д. О. Шпилевский (Proceedings of the National Academy of Sciences of Belarus. Agrarian Series, 2019)
Rabies is absolutely lethal acute viral disease that affects humans and all warm-blood animals, which is common in many countries of the world, including Belarus. Wild carnivorous animals, mainly foxes, are the main source of rabies virus infection, therefore development and improvement of means and methods for preventing this disease among wild carnivores, in particular oral immunization of carnivorous animals, is of great research and practical importance. Anti-rabies vaccine was developed for oral use in the form of a blister-free bait consisting of fixed rabies virus selected by us – strain KMIEV-94 (71 BelNIIEV–VGNKI M), meat and bone meal and wheat flour, gelatin, glycerin and tetracycline. Technology for manufacture of improved highly immunogenic blister-free vaccine-containing bait for oral vaccination of wild carnivorous animals against rabies was developed. Immunological and anti-epizootic efficiency of vaccine-containing baits was studied. It was determined that use of the developed vaccine-containing blister-free anti-rabies bait in natural conditions is ecologically safe, since KMIEV-94 rabies virus is deeply attenuated and apathogenic for rodents and carnivorous animals after oral administration, does not have reversibility and after 9 days of storing the bait at a temperature of 18–20 °C is inactivated. High efficiency, safety, simple manufacturing technology of the developed bait indicate prospects of its introduction into practice, which will reduce the incidence of rabies in animals. Бешенство – абсолютно смертельное острое вирусное заболевание, поражающее человека и всех теплокровных животных, которое распространено во многих странах мира, в том числе и в Беларуси. Основным источником заражения вирусом бешенства являются дикие плотоядные животные, главным образом лисицы, поэтому разработка и усовершенствование средств и методов профилактики указанного заболевания среди диких плотоядных животных, в частности пероральной иммунизации плотоядных животных, имеет важное научно-практическое ...